Safety and pleasure motives determine perceived risks and rewards in casual sex - Rodrigues, D. L. (2024)
People differ in their predispositions to value safety maintenance (i.e., disease prevention regulatory focus) or pleasure pursuit (i.e., pleasure promotion regulatory focus). Extending recent research, results of a cross-sectional study with participants living in Portugal and Spain (N = 770) showed that these individual differences resulted in a trade-off between potential health risks and pleasure rewards in sexual practices and experiences with casual partners. Specifically, people who were more focused on promotion (vs. prevention) reported riskier and more unrestricted sexual activities (more frequent condomless sex activities; more casual partners) and experienced more positive sexual outcomes (more sexual satisfaction; more positive and less negative affect related to condomless sex). This pattern of results remained the same after controlling for country differences, suggesting the robustness of our findings across different cultural contexts. Our study shows the complexity of sexual decisions and align with our reasoning that prevention-focused people tend to prioritize health safety, whereas promotion-focused people tend to prioritize sexual pleasure. Theoretical and applied implications are discussed.